2016
DOI: 10.1002/asia.201600102
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Polysubstituted Benzenes through a N,N‐dimethyl‐4‐aminopyridine (DMAP)‐Catalyzed [4+2] Benzannulation of 1,3‐Bis(sulfonyl)butadienes and γ‐Substituted Allenoates

Abstract: A new strategy for the one-pot synthesis of polysubstituted benzenes through a N,N-dimethyl-4-aminopyridine (DMAP)-catalyzed [4+2] benzannulation from readily prepared 1,3-bis(sulfonyl)butadienes and γ-substituted allenoates is described. This method provides a facile, metal-free and general route to highly substituted benzenes under mild conditions in moderate-to-good yields with complete regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…For example, in 2016, Huang's group disclosed an efficient method to attain polysubstituted benzenes 84 via the annulation of dienic sulfones 82 and a-substituted allenoates 83 (Scheme 24). 44 The reaction proceeded successfully with DMAP as the catalyst and CH 3 COONa as the additive in CHCl 3 at 60 C. Various substituents on 82 or 83 were well tolerated, providing product 84 in acceptable-to-good yields (29-72%) with high regioselectivity. However, low yields were observed when the benzene core beard an electron-decient (NO 2 ) or an electron-rich group (OMe).…”
Section: [4 + 2] Benzannulationmentioning
confidence: 96%
“…For example, in 2016, Huang's group disclosed an efficient method to attain polysubstituted benzenes 84 via the annulation of dienic sulfones 82 and a-substituted allenoates 83 (Scheme 24). 44 The reaction proceeded successfully with DMAP as the catalyst and CH 3 COONa as the additive in CHCl 3 at 60 C. Various substituents on 82 or 83 were well tolerated, providing product 84 in acceptable-to-good yields (29-72%) with high regioselectivity. However, low yields were observed when the benzene core beard an electron-decient (NO 2 ) or an electron-rich group (OMe).…”
Section: [4 + 2] Benzannulationmentioning
confidence: 96%
“…In 2016, Huang and co-workers reported a DMAP-catalyzed (4 + 2) benzannulation from readily prepared 1,3-bis(sulfonyl) butadienes 11 and γ-substituted allenoates 12. [32] When only DMAP was used as catalyst, the multi-substituted cyclohexene 46 a and cyclohexadiene derivative 47 a were obtained in moderate yields. It was found that the additives including inorganic bases (e. g., CH 3 CO 2 Na, NaOH, Cs 2 CO 3 ), organic bases (e. g., NEt 3 , DIPEA) as well as Brønsted acid (PhCOOH) could switch the selectivity of the benzannulation reaction to generate the polysubstituted benzenes 48 (Scheme 9).…”
Section: Tertiary Amine-mediated Benzannulation Reactionsmentioning
confidence: 99%
“…Recently, Huang and co‐workers demonstrated a DMAP‐catalyzed [4+2] benzannulation reaction of 1,3‐bis(sulfonyl)butadienes 136 with γ‐substituted allenoates 137 for the regioselective synthesis of polysubstituted benzenes 138 by using 30 mol % CH 3 COONa as an additive (Scheme ) . Dienic sulfones that contained a moderately electron‐donating group (CH 3 ) or an electron‐withdrawing group (Br, Cl, F, or CF 3 ) on the benzene ring afforded the corresponding benzannulated derivatives in moderate‐to‐good yields.…”
Section: Dmap‐mediated Benzannulation Reactionsmentioning
confidence: 99%